Educational briefings in touristic facilities promote tourist sustainable behavior and customer loyalty. (July 2021) - Meschini, Marta; Machado Toffolo, Mariana; Caroselli, Erik; Franzellitti, Silvia; Marchini, Chiara; Prada, Fiorella; Boattini, Alessio; Brambilla, Viviana; Martinez, Grit; Prati, Francesca; Simoncini, Ginevra; Visentin, Marco; et al.
Abstract: Ecotourism gives tourists the opportunity to improve knowledge and awareness of environmental issues while on vacation. Recreational environmental education has been proven an effective method to raise perception of human impact on ecosystems. "Glocal Education" is an education project aimed at developing environmental interest in tourists on vacation. The present study assessed the effectiveness of Glocal Education in improving tourist environmental interest. Using specific questionnaires, we evaluated project impact on tourists, tourist satisfaction regarding the project and customer loyalty towards the tour operator hosting the project. The study took place at three mass touristic facilities, where tourists were asked to fill a questionnaire before and after participating in educational activities (e.g., biology lessons, excursions). The average score of both questionnaires was then compared to evaluate possible improvement of tourist knowledge, attitude and awareness. Results showed that such activities had a significantly positive impact on tourist knowledge, attitude and awareness at all localities. High levels of satisfaction and loyalty towards the host tour operator were observed at all sites, which indicate that once a person is briefed about the correct approach to natural systems, they can become increasingly interested in taking action, developing an "advocate" role. This study shows how informal education activities can act as trigger for environmental awareness and behavior among tourists, providing them with the tools, knowledge, and motivation to critically discern what is and isn't environmentally friendly, not only in terms of products and services in their everyday life, but also when choosing their vacation spots. Highlights: Recreational briefings increased tourists' knowledge about the environment. Recreational briefings educated tourists for an environmentally friendly attitude. Recreational briefings enhanced tourists' environmental awareness. Tour operators benefit from offering environmental educational projects. Most tourists have enjoyed learning about nature during their holiday.